Genetic Characterization of Raspberry Bushy Dwarf Virus Isolated from Red Raspberry in Kazakhstan - Mariya Kolchenko; Anastasiya Kapytina; Nazym Kerimbek; Alexandr Pozharskiy; Gulnaz Nizamdinova; Marina Khusnitdinova; Aisha Taskuzhina; Dilyara Gritsenko (Viruses, 2023)
Raspberry bushy dwarf virus (RBDV) is an economically significant pathogen of raspberry and grapevine, and it has also been found in cherry. Most of the currently available RBDV sequences are from European raspberry isolates. This study aimed to sequence genomic RNA2 of both cultivated and wild raspberry in Kazakhstan and compare them to investigate their genetic diversity and phylogenetic relationships, as well as to predict their protein structure. Phylogenetic and population diversity analyses were performed on all available RBDV RNA2, MP and CP sequences. Nine of the isolates investigated in this study formed a new, well-supported clade, while the wild isolates clustered with the European isolates. Predicted protein structure analysis revealed two regions that differed between α- and β-structures among the isolates. For the first time, the genetic composition of Kazakhstani raspberry viruses has been characterized.